The Dynamics of Innovative Activity and Competitive Advantage: The Case of Australian Retail Banking, 1981 to 1995 - Roberts, Peter W.; Amit, Raphael (Organization Science, 2003)
This study examines the adoption of new products and processes in the Australian retail banking industry over the 1981 to 1995 period. Our analysis demonstrates that the vast majority of observed innovative activity was based on ideas sourced from outside the focal firm, and that innovations diffused very quickly across competing banks. As such, there were no periods during which any bank had proprietary possession of a major product or process innovation. We therefore ask how the banks' innovative activity could affect their relative financial performance positions. We answer this question by developing a set of hypotheses that relate specific features of their histories of innovative activity to their current financial performance. These hypotheses are tested using a detailed data set describing 1,297 modifications made to products and services, distribution technologies, and back-office processes within a sample of Australian retail banks over the sample period. Our results provide support for the general position that establishing an attractive competitive position depends on the specific history of a firm's innovative activity. Banks that undertook more innovative activity, that were more consistent in that activity, and whose composition of activity was somewhat differentiated from the industry norm tended to display superior financial performance. Rather than looking solely for internally generated, inimitable innovations to deliver competitive advantage, these results suggest that active and consistent innovative activity that is somewhat differentiated from competitors can also deliver superior financial performance.